2021
DOI: 10.1162/jocn_a_01690
|View full text |Cite
|
Sign up to set email alerts
|

Motor Inhibition to Dangerous Objects: Electrophysiological Evidence for Task-dependent Aversive Affordances

Abstract: Previous work suggests that perception of an object automatically facilitates actions related to object grasping and manipulation. Recently, the notion of automaticity has been challenged by behavioral studies suggesting that dangerous objects elicit aversive affordances that interfere with encoding of an object's motor properties; however, related EEG studies have provided little support for these claims. We sought EEG evidence that would support the operation of an inhibitory mechanism that interferes with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…In the field of affordance perception, there has been debate regarding whether it is an automated process or not. Some researchers argue that affordance perception is an automatic process due to its fast and effortless nature (Tucker & Ellis, 1998; Goslin, Dixon, Fischer, Cangelosi, & Ellis, 2012; Bonner & Epstein, 2017; Harel, Nador, Bonner, & Epstein, 2022), whereas others suggest that it is not automated but rather highly contextualized and can be influenced by biases and expectations (Tipper, Paul, & Hayes, 2006; Girardi, Lindemann, & Bekkering, 2010; Pellicano, Iani, Borghi, Rubichi, & Nicoletti, 2010; Kalénine, Wamain, Decroix, & Coello, 2016; Wokke, Knot, Fouad, & Ridderinkhof, 2016; Mustile, Giocondo, Caligiore, Borghi, & Kourtis, 2021). However, a synthesis perspective proposes that affordance automaticity should be understood as a dynamic process that changes over time, whereby affordance perception may initially occur automatically but is later modulated by higher-level cognitive processes (Borghi & Riggio, 2015; Kourtis, Vandemaele, & Vingerhoets, 2018; Gastelum, 2020; Djebbara et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of affordance perception, there has been debate regarding whether it is an automated process or not. Some researchers argue that affordance perception is an automatic process due to its fast and effortless nature (Tucker & Ellis, 1998; Goslin, Dixon, Fischer, Cangelosi, & Ellis, 2012; Bonner & Epstein, 2017; Harel, Nador, Bonner, & Epstein, 2022), whereas others suggest that it is not automated but rather highly contextualized and can be influenced by biases and expectations (Tipper, Paul, & Hayes, 2006; Girardi, Lindemann, & Bekkering, 2010; Pellicano, Iani, Borghi, Rubichi, & Nicoletti, 2010; Kalénine, Wamain, Decroix, & Coello, 2016; Wokke, Knot, Fouad, & Ridderinkhof, 2016; Mustile, Giocondo, Caligiore, Borghi, & Kourtis, 2021). However, a synthesis perspective proposes that affordance automaticity should be understood as a dynamic process that changes over time, whereby affordance perception may initially occur automatically but is later modulated by higher-level cognitive processes (Borghi & Riggio, 2015; Kourtis, Vandemaele, & Vingerhoets, 2018; Gastelum, 2020; Djebbara et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reach phase duration, previous studies have demonstrated motor inhibition when approaching dangerous objects due to the emergence of aversive affordances (Mustile et al, 2021 ). Furthermore, from visual search research, it is known that violations of one's scene grammar lead to longer and more fixations on the critical objects, which is typically attributed to more extended processing of those objects (Henderson et al, 1999 ; Cornelissen and Võ, 2017 ; Draschkow and Võ, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies demonstrated that reaching an object before grasping it can be affected by various factors. As an example, motor inhibition when approaching dangerous objects has been shown due to the emergence of aversive affordances (Mustile et al, 2021 ). These studies provide evidence that the way we look at and grasp objects around us might differ depending on the meaning of that object and the semantic context they are placed.…”
Section: Introductionmentioning
confidence: 99%
“…Gibson (1979) used the term “affordance” earliest to indicate the potential actions elicited by the observation of objects in the environment. The orientation of object graspable parts ( Tucker and Ellis, 1998 ), the object size and graspability ( Anelli et al, 2013a ), the perceived distance of an object ( Mustile et al, 2021 ), or its harmfulness ( Anelli et al, 2012a ) are all aspects influencing affordances.…”
Section: Introductionmentioning
confidence: 99%